2019
DOI: 10.3389/fmars.2019.00377
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Weight of Evidence Approach for Monitoring Complex Environmental Scenarios: the Case-Study of Off-Shore Platforms

Abstract: Weight of Evidence (WOE) Approach for Monitoring indices. The WOE integration of multiple typologies of data allowed more robust and weighted conclusions compared to the use of individual LOEs, highlighting the feasibility of this procedure for multidisciplinary monitoring and risk assessment approaches. On a practical side, the WOE evidences also suggested a revision of actual monitoring procedures. Overall, the proposed WOE model appeared as a useful tool to summarize large datasets of complex data in integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 44 publications
1
49
0
1
Order By: Relevance
“…Similarly, biological evaluations are not based on variations of individual responses, thus providing a more integrated assessment of the ecotoxicological or ecological hazards. As recently shown in a complex monitoring scenario of off-shore platforms (Regoli et al, 2019), this study confirmed the practical importance of a transparent procedure combining a scientifically sound approach with the possibility to synthesize the overall significance of the results obtained. Concerning the different typologies of the results obtained in the present study on the coastline of Finland the WOE integration summarized a "Slight" environmental impact in half of the study areas (Vaasa, Pori, Uusikaupunki, Hanko, and Helsinki) and "Moderate" in the other ones, none of the sites showing "Major" or "Severe" impacts.…”
Section: Woe Elaborationsupporting
confidence: 81%
See 1 more Smart Citation
“…Similarly, biological evaluations are not based on variations of individual responses, thus providing a more integrated assessment of the ecotoxicological or ecological hazards. As recently shown in a complex monitoring scenario of off-shore platforms (Regoli et al, 2019), this study confirmed the practical importance of a transparent procedure combining a scientifically sound approach with the possibility to synthesize the overall significance of the results obtained. Concerning the different typologies of the results obtained in the present study on the coastline of Finland the WOE integration summarized a "Slight" environmental impact in half of the study areas (Vaasa, Pori, Uusikaupunki, Hanko, and Helsinki) and "Moderate" in the other ones, none of the sites showing "Major" or "Severe" impacts.…”
Section: Woe Elaborationsupporting
confidence: 81%
“…Data on water chemistry, bioaccumulation and variations of biomarkers in caged mussels as well as benthic community status were elaborated within the WOE model, which summarizes hazard indices for various LOEs in specific modules before their overall integration. The computation rules of the WOE model have been successfully applied to classify environmental hazards in different conditions of origin, typology, and intensity of pollution, including highly and moderately contaminated sites from industrial areas, harbors, brackish environments, and the Costa Concordia shipwreck on the Italian coast (Piva et al, 2011;Benedetti et al, 2012Benedetti et al, , 2014Regoli et al, 2014;Bebianno et al, 2015), and most recently in the assessment of environmental effects of offshore oil platforms in the Adriatic Sea (Regoli et al, 2019) In the latter paper, full and updated descriptions of the LOE/WOE calculation methodologies are presented.…”
Section: The Woe Approachmentioning
confidence: 99%
“…Confounding factors such as exposure to wastewater or stormwater inputs that also release terrestrial fatty acids into the marine environment need to be taken into consideration when interpreting results. Regoli et al (2019) demonstrated the use of the weight-ofevidence model, Sediqualsoft, to provide quantitative hazard indices using data collected at three off-shore oil platforms in the southern Adriatic Sea. Data included sediment chemistry, bioaccumulation and biomarkers (digestive gland metallothionein [MT, metal exposure], CAT, GST, GPx, GR, glutathione, total antioxidant capacity and LPO and hemocyte AChE, LMS, phagocytosis, granulocyte:hyalinocyte ratio [immune function], and DNA damage [comet assay and micronuclei]) in native and transplanted mussels (M. galloprovincialis), bioaccumulation in laboratory-exposed polychaetes (Hediste diversicolor), elutriate bioassays with four species (Vibrio fischeri, Acartia tonsa, Phaeodactylum tricornutum and Paracentrotus lividus), and benthic community analyses, resulting in about 7000 individual data points from 60 sites.…”
Section: Fishmentioning
confidence: 99%
“…Bagnoli has served as the subject of numerous scientific studies aimed at verifying the current condition of the water and marine sediments present in the GoP. Recent work has focused on bioaccumulation and biomarkers investigations to better understand the toxic effects and mechanism of action of contaminants [10][11][12]. Recently, an integrated assessment called sediment quality triad (SQT) was used to consider chemical analyses and biological effects as different lines of evidence (LOEs) to describe environmental quality of marine sediments [2,13].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an integrated assessment called sediment quality triad (SQT) was used to consider chemical analyses and biological effects as different lines of evidence (LOEs) to describe environmental quality of marine sediments [2,13]. A multidisciplinary approach (the weight of evidence approach, WoE) permits researchers to interpret various environmental conditions compared to a univariate analysis, such as a chemical approach, and circumvent overestimated and costly management decisions [11]. The WoE approach, integrating five lines of evidence (LOEs: sediment chemistry, bioavailability of chemicals, subcellular effects, toxicity at organism level and at the community level) was successfully applied to the Bagnoli case study and revealed a clearly polluted area but less critical levels of pollution when compared to the results of sediment chemistry alone [2].…”
Section: Introductionmentioning
confidence: 99%